Comparing 3D Virtual Labs and Traditional Labs: Impact on Teacher Training and Student Learning in Physics Education - Sarapak, Choojit; Jumpatam, Jutapol; Lunnoo, Thodsaphon; Kongngarm, Nipasak; Raso, Sayam; Kearns , Kevin (Jurnal Pendidikan IPA Indonesia, 2025)
Experiments are fundamental to physics education but are often hindered by resource constraints. This study investigates the effectiveness of teacher training using 3D Virtual Labs (3DVL) compared to Traditional Labs (TL) in teaching the electron charge-to-mass ratio (e/m). The research aimed to quantitatively compare the impact of these methods on teachers' and students' conceptual understanding, critical thinking, and experimental skills. A quasi-experimental design was employed involving 32 teachers and 131 students, utilizing a pre-test/post-test comparison structure. Teachers received training in either 3DVL or TL methods before applying the instruction in their classrooms. The results indicate that both 3DVL and TL groups improved significantly (p < .001) in conceptual mastery and problem-solving abilities. While no statistically significant difference was observed between the groups’ overall post-test scores, TL showed a slight advantage in problem-solving, whereas 3DVL was associated with higher student confidence and perceived experimental skill improvement. These findings suggest that 3DVL is a viable, cost-effective alternative to traditional equipment. The study concludes that integrating virtual simulations can effectively overcome infrastructure limitations and enhance learning outcomes in resource-constrained settings.